Extractos de las Hojas de Salvia officinalis y Sambucus peruviana H.B.K. como Inhibidores de Incrustación - Castillo Campos, Luis Antonio; Barreto, Steevenson José (Ingeniería, 2020)
Context: The phenomenon of scale formation has become one of the operational problems with the highest frequency of occurrence in the oil industry, and the search for innovative sources of mitigation has proved to be the horizon to which the companies in the area have pointed. This is the reason why in this investigation the anti-fouling effect that the extracts of the Salvia officinalis and Sambucus peruviana H.B.K leaves was evaluated. Method: The physicochemical characterization of a production water sample of the Oritupano Oilfield was performed and the extracts were obtained, and then its physical properties were identified. Next, the inhibitory performance of each natural product was determined together with a commercial agent, all through the application of the NACE Standard TM0374-2007, in addition to applying a statistical analysis to visualize the significant differences that could be present between the experimental and commercial efficiencies. Results: Extracts of Salvia officinalis and Sambucus peruviana H.B.K used as antiscaling externalized acidic pH results and viscosities below 2 cSt; showing maximum performances of 87,27% and 90,91% for solutions based on elderberry and sage respectively and statistical behaviors similar to the referential commercial product. Conclusions: In quantitative terms, the sage-based product was more effective when evaluated in the Oritupano oilfield production water sample, showing a directly proportional concentration - efficiency behavior, in addition to exposing characteristics more consistent with a Calcium Carbonate scale bioinhibitor, although with a proportion of solids that should be reduced, requiring that this characteristic be improved in the future and the joint action of both extracts can be measured in the prevention of scale, both experimentally and in the field.